Application of Artificial Intelligence with Ant Colony Algorithm in construction projects schedule - Kiana Ahghari (مهندسی و مدیریت ساخت)
Today, using project management methods and tools to realize the goals of many organizations and companiesIt is essential. Scheduling of activities, to minimize costs by using limited resources and inConditions of existence of time-sensitive constraints are used. These methods are the ability of the organizationThey improve the implementation and control of projects and ways to use resources and individuals. Many methodsThe existing scheduling of the activities of a project is applicable, while complicatedMany organizations face the challenge of managing multiple projects simultaneously. So useMethodology of Scheduling of Projects with Artificial Intelligence and with the Approach of Ant Colony Algorithm for Organizations MethodOptimal and practical among other methods. In this article, the methods of solving and characteristics of issuesThe timing of the projects and the work done in this area has been studied and compared. AtThe results of this study are presented at the end of this study and future research fields have been introduced.